Análise de ação educativa sobre vigilância do óbito infantil para profissionais da saúde do Estado do Maranhão - Perez, Caroline Wey [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
ABSTRACT This study aimed to analyze an educational action on reducing child death in the city of São Luís, in the State of Maranhão, Brazil, from the perspective of its participants. This activity was carried out in 2014, in the form of classroom and distance learning education and makes up a large permanent health education project, entitled "Surveillance of maternal and child health: educational action to reduce infant mortality, from the epidemiological reality of selected states." This project was prepared and implemented in a teacher partnership of the Department of Nursing, Botucatu Medical School, Universidade Estadual Paulista and by responsible parties in the Surveillance Technical Area of the Ministry of Health and the State Department of Health of São Luís. Through the qualitative approach, in the first half of 2015, 17 participants of that action were interviewed, coming from different points in the network of attention and vigilance in maternal and child health of the municipality in question. The data were organized in accordance with the Content Analysis Method, in a thematic strand and analyzed based on principles of continuing education in health and scientific production through current technical surveillance on maternal and child health and infant mortality. The research project was approved by the Ethics Committee of the Botucatu School of Medicine - UNESP. The statements obtained were organized in three main areas: 1. Surveillance of infant death as a process to qualify attention to maternal and child health; 2. The educational activity as a facilitator of learning strategy on surveillance of infant death; 3. Implications of experience on professional development and health services. The core meanings of these themes revealed enlarged conceptions, but limited experience regarding the realization of monitoring in maternal and child health. For participants, the educational activity contributed to the significant learning of the content addressed by employing innovative and active methods, and considering the professional reality of the content. There was emphasis on the complementation of theoretical and practical knowledge on the subject and also on the proposition, implementation and results of operations appropriate to solving problems of attention to maternal and child health and monitoring of infant death. Considering these findings and in accordance with the participants of this study, it is recommended to continue the educational process at the local level, expanding participation to other professional care and health management.

Este estudo objetivou analisar uma ação educativa sobre redução do óbito infantil no município de São Luís, estado do Maranhão, Brasil, na perspectiva de seus participantes. Essa ação educativa foi realizada em 2014, sob a modalidade de ensino presencial e à distância e compõe um amplo projeto de educação permanente em saúde, intitulado “Vigilância em saúde materno-infantil: ação educativa para redução do óbito infantil, a partir da realidade epidemiológica de estados selecionados”. Este projeto foi elaborado e executado em parceria de docentes do Departamento de Enfermagem da Faculdade de Medicina de Botucatu da Universidade Estadual Paulista e de responsáveis pela Área Técnica de Vigilância em Saúde do Ministério da Saúde e da Secretaria Estadual de Saúde de São Luís.Por meio da abordagem qualitativa de pesquisa, no primeiro semestre de 2015, foram entrevistados 17 participantes da referida ação, advindos de diferentes pontos da rede de atenção e vigilância em saúde materno-infantil do município em foco. Os dados foram sistematizados segundo o Método de Análise de Conteúdo, numa vertente temática e foram analisados com base em princípios da educação permanente em saúde e na produção científica e técnica atual sobre vigilância em saúde materno-infantil e do óbito infantil. O projeto desta pesquisa obteve parecer favorável do Comitê de Ética em Pesquisa da Faculdade de Medicina de Botucatu – UNESP. Os depoimentos obtidos foram sistematizados em três grandes temas: 1. Vigilância do óbito infantil como processo para qualificar a atenção à saúde materno-infantil; 2. A ação educativa como estratégia facilitadora da aprendizagem sobre a vigilância do óbito infantil; 3. Implicações da experiência quanto ao desenvolvimento profissional e para os serviços de saúde. Os núcleos de sentido destes temas revelaram concepções ampliadas, porém experiências restritas quanto à realização da vigilância em saúde materno-infantil. Para as participantes, a ação educativa contribuiu para a aprendizagem significativa do conteúdo abordado, ao empregar métodos ativos, inovadores e considerando a realidade profissional dos mesmos. Houve destaque para a complementação do conhecimento teórico e prático sobre o tema e, também, quanto à proposição, implementação e resultados de operações apropriadas para solução de problemas relativos à atenção à saúde materno-infantil e à vigilância do óbito infantil. Considerando os achados deste estudo e em acordo com as participantes do mesmo, recomenda-se a continuidade do processo educativo em nível local, ampliando a participação para outros profissionais da atenção e gestão em saúde.
Analysis of educational action of infant mortality surveillance for health professionals of the State of Maranhão
Keywords: Public health surveillance; Maternal and child health; Child mortality; Education, Continuing; Public health nursing; Vigilância em saúde pública; Saúde Materno-Infantil; Mortalidade Infantil; Educação Permanente; Enfermagem em Saúde Pública